PENERAPAN MODEL PEMBELAJARAN QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV MI AL-MUHAJIRIN MENGGALA SAKTI - Herlinawati, Herlinawati; Alpusari, Mahmud; Marhadi, Hendri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Problem Research is low results Students learn science class IV MI Al Muhajirin Menggala sakti That is an average of 57.75 With The KKM 70. This about caused teachers Still Less Varies in using Model Or development strategi in proces’s Learning that Students involved resuld Less Active While studying. This research in Shape Classroom Action Research (PTK). This research aims to improve learning IPA IV MI Al-Muhajirin Menggala Sakti. The formulation of the problem